Coastal management - putting policy into practice proceedings of the conference organised by the Institution of Civil Engineers and held in Bournemouth on 12-14 November 1995 - Fleming, C. A. 1916-1987 (Thomas Telford, 1996)
These conference proceedings from the coastal management conference include information on policy including the House of Commons Environment Committee Report on coastal zone protection and planning, a number of consultative documents, and details on new guidelines and policies which have had a significant impact on the coastal community.